\( 1 \quad \frac { 2 a + 3 b } { 9 } + \frac { a - 4 b } { 6 } \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the expression \( \frac { 2 a + 3 b } { 9 } + \frac { a - 4 b } { 6 } \), we first need a common denominator. The least common multiple of 9 and 6 is 18. Rewriting the fractions, we get: \( \frac { 2a + 3b } { 9 } = \frac { 2a + 3b } { 9 } \cdot \frac { 2 } { 2 } = \frac { 4a + 6b } { 18 } \) and \( \frac { a - 4b } { 6 } = \frac { a - 4b } { 6 } \cdot \frac { 3 } { 3 } = \frac { 3a - 12b } { 18 } \). Now, we can combine the two fractions: \[ \frac { 4a + 6b } { 18 } + \frac { 3a - 12b } { 18 } = \frac { (4a + 6b) + (3a - 12b) } { 18 } = \frac { 4a + 3a + 6b - 12b } { 18 } = \frac { 7a - 6b } { 18 }. \] Thus, the simplified expression is \( \frac { 7a - 6b } { 18 } \).